Keamanan pada Grid Computing~Survey Paper - Ghufran Ibnu Yasa (Elkawnie, 2015)
Grid computing provides high computing power, enormous data storage, and collaboration possibilities to its users. Grid computing is currently in the midst of evolving standards, inheriting and customizing from those developed in the high performance, distributed, and recently from the Web services community. Grid computing is widely regarded as a technology of immense potential in both industry and academia. Which this interest, security become necessery to provide authentication, authorization, resource protection, secure communication, data integrity, trust management and network security. This paper tells about progression of the security system on grid computing by conducting a survey of existing paper and applications have been developed.